The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1161/strokeaha.111.638379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Length of Recovery of Pusher Syndrome Based on Cerebral Hemispheric Lesion Side in Patients With Acute Stroke

Abstract: The number of RCD patients who exhibited PB was higher than that of LCD patients. The duration of recovery from PB was longer in RCD patients than in LCD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 8 publications
2
51
0
9
Order By: Relevance
“…Incidence of the unilateral neglect in patients with acute stroke was assess by SiekierkaKleiser et al: 32.69% [19]. Pusher syndrome was observed in 9.4-28% post-stroke survivors [20][21][22]. According to the recent review of Allison et al, incidence of spasticity in poststroke survivors with weakness ranged from 33% to 78%, and contractures were present in >50%.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of the unilateral neglect in patients with acute stroke was assess by SiekierkaKleiser et al: 32.69% [19]. Pusher syndrome was observed in 9.4-28% post-stroke survivors [20][21][22]. According to the recent review of Allison et al, incidence of spasticity in poststroke survivors with weakness ranged from 33% to 78%, and contractures were present in >50%.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers [36][37][38] have also found that patients with right hemispheric lesions seem to display the poorest postural control. Abe et al [39] found significantly higher prevalence for pushing behavior, a disorder of the upright body orientation with respect to gravity [39,40], in patients with acute right hemispheric lesions as compared to left and thereby poorer postural control. We have only found two studies on hemispheric asymmetry related specifically to trunk control in stroke, and these demonstrated poorer postural stability in sitting in patients with right hemispheric lesions as compared to left [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Abe et al 1 regarding the prevalence and length of recovery of pusher behavior (PB) in patients with acute stroke. Their retrospective cohort study included 1660 patients with acute stroke.…”
Section: To the Editormentioning
confidence: 99%
“…1 Authors have used the Stroke Impairments Assessment Set as the only method to assess neglect. It is widely discussed that using several tests is a more reliable way to uncover evidence of neglect than a single test and the sensitivity of the Stroke Impairments Assessment Set for neglect could be questioned.…”
Section: To the Editormentioning
confidence: 99%